Historic cities issues in urban conservation - Cody, Jeffrey W. 1950-; Siravo, Francesco (The Getty Conservation Institute, 2019)
"This book presents a comprehensive selection of important writings on urban conservation, as distinct from both heritage conservation and urban planning. There are more than sixty-five texts, ranging from early polemics by Victor Hugo and John Ruskin to a generous selection of recent scholarship, covering North America, Europe, India, China, Japan, Africa, and the Islamic world"...Provided by publisher
Includes bibliographical references and index
Keywords: Historic preservation; Cities and towns; City planning; Stadtplanung; Historische Stätte; Denkmalschutz; Kulturerbe; Stadt; Aufsatzsammlung